Evolusi Pembiayaan Mudharabah Sebagai Instrumen Halal National Fund - Zaki, Khozin; Handani, Rani; Hardianti, Iin Julia (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2021)
At present, in a competitive Islamic financial system, mudarabah (profit sharing) is seen as an alternative mechanism in Indonesia. Since it was introduced mudarabah (profit sharing) has gone through various evolutions to meet the rapidly growing needs of Islamic finance. However, in the current Islamic financial system, mudarabah (profit sharing) is less desirable by the public. This is due to the asymmetric information that is continuously presented in mudarabah (profit sharing) contracts and creates adverse selection problems. Therefore, mudarabah (profit sharing) has rejected its importance as a financing vehicle. Therefore, the purpose of this paper is to analyze the thinking and evolution of mudarabah financing in Islamic banking from the perspective of classical and contemporary Islamic studies and evaluate the risk prevention of mudarabah financing in Indonesia also the development of halal national funds using this instrument. The writing method used is a literature study that looks for theoretical references that are relevant to the topic raised through the method of collecting library data by reading through journals. Mudarabah is one of the important methods of Islamic financing that is widely used in various fields of Islamic finance and has a strategical position on halal national fund development.